Kissing, Saliva and Human Papilloma Virus: Principles, Practices, and Prophylaxis - Touyz, Louis Z.G.; Touyz, Sarah J.J. (Jour Med Resh and Health Sci, 2020)
Introduction: Kissing is a globally practiced form of communication, yet saliva is often deemed a harmless bodily fluid. Many viruses thrive in salivary and oro-pharyngeal lymphoid cells. These viruses include Human Papilloma Virus (HPV), Human Herpes Viruses, Epstein –Barr, HIV, Polio and others, and are transmitted between people when kissing. Aim: This appraisal (1)assesses socially sanctioned kissing habits, (2) examines the presence of Human Papilloma Virus [HPV] in saliva and salivary tests for HPV, (3) reviews protection from HPV vaccines, (4)deconstructs attitudes and behavior, and critiques the oncogenic potential of HPV morbidity from peri-osculation practices. Materials and Methods: Clinical- tests for putative HPV viruses in oro-pharyngeal cancers use saliva to detect HPV oncogenic types; these re-affirm presence of HPV’s in saliva, and their causal relationship to the majority of head and neck cancers. Conclusion: Although frequency of new infections from kissing is unknown, this critique suggests caution against random kissing, encourages use of HPV vaccination for prophylaxis, and indicates that this may moderate HPV and viral transmission, with consequent reduction of HPV morbidity and mortality.